Loop diuretics, renal function and clinical outcome in patients with heart failure and reduced ejection fraction. (23rd December 2015) - Damman, Kevin; Kjekshus, John; Wikstrand, John; Cleland, John G.F.; Komajda, Michel; Wedel, Hans; Waagstein, Finn; McMurray, John J.V.
Abstract : Aim: We aimed to study the relationships of loop diuretic dose with renal function and clinical outcomes in patients with chronic heart failure (HF). Methods and results: Loop diuretic dose at baseline was recorded in patients included in the Controlled Rosuvastatin Multinational Trial in Heart Failure (CORONA). The relationship to change in estimated glomerular filtration rate (eGFR) over time and to the first occurrence of the composite outcome of cardiovascular (CV) death or hospitalization owing to HF was examined in propensity score matched cohorts. Of the 5011 patients, 2550, 745, and 449 were receiving >80 mg (high), 41–80 mg (medium) and ≤40 mg (low) of loop diuretics in furosemide equivalent daily dosages, respectively, which were used to assemble 229, 385, and 1045 pairs of propensity‐matched high, medium, and low dose cohorts. Compared with matched no loop diuretic groups, eGFR declined 0.3 ± 0.2, 0.3 ± 0.3 and 1.2 ± 0.5 mL/min/1.73 m 2 /year in the low‐, medium‐, and high‐dose groups, respectively. Compared with matched no loop diuretic groups, hazard ratios (HR) (95% confidence intervals) for outcome associated with low‐, medium‐ and high‐dose groups were 1.71 (1.41–2.06), 1.99 (1.50–2.64), and 2.94 (1.95–4.41), respectively. Higher loop diuretic dose was particularly associated with increased risk for hospitalization owing to HF: HR 4.80 (2.75–8.37), P  < 0.001. Conclusions: The use of loop diuretics was associated with a slightly greater rate of decline in eGFR, which did not vary significantly by diuretic dose.Loop diuretic dose was associated with higher risks of (CV) mortality and predominantly hospitalization owing to HF, which appeared to be higher among those receiving higher daily doses.